Brain‐derived neurotrophic factor promotes proliferation and progesterone synthesis in bovine granulosa cells. Issue 6 (19th November 2018) - Chen, Shuxiong; Wang, Fengge; Liu, Zhuo; Zhao, Yun; Jiang, Yanwen; Chen, Lu; Li, Chunjin; Zhou, Xu
Abstract: Brain‐derived neurotrophic factor (BDNF) is involved in regulating the growth of ovarian follicles, maturation of the oocyte, and development of the early embryo through its receptor, tyrosine kinase receptor B (TrkB). However, it is still unclear as to how BDNF influences proliferation and steroidogenesis of bovine granulosa cells (GCs). In this paper, we confirmed that BDNF and TrkB were expressed in bovine GCs, and that proliferation and steroidogenesis by bovine GCs were reduced by knockdown of BDNF or inhibition of TrkB. With respect to GC proliferation, BDNF enhanced cellular viability and the percentage of cells in the S phase. BDNF also activated both protein kinase B (PKB, also known as AKT) and the extracellular signal‐regulated protein kinase 1/2 (ERK1/2)‐signaling pathway. Through the AKT‐signaling pathway, BDNF increased the expression of proliferation‐related genes, including cyclin A1 (CCNA1), cyclin E2 (CCNE2), cyclin D1 (CCND1), and cyclin‐dependent kinase 1 (CDK1). However, through the ERK1/2 signaling pathway, BDNF only increased the expression of CCNA1 and CCNE2. Regarding steroidogenesis by bovine GCs, BDNF promoted progesterone (P 4 ) synthesis, but had no effect on estradiol; it also activated the AKT‐signaling pathway and increased the expression of steroidogenesis‐related genes, including steroidogenic acute regulatory protein (STAR) and hydroxy‐δ‐5‐steroid dehydrogenase, 3β‐ and steroid δ‐isomerase 1 (HSD3B1). In summary, our data are the first to show that BDNF promotes the proliferation of bovine GCs through TrkB–AKT and ERK1/2 signaling pathways and increases P4 synthesis by bovine GCs through the TrkB–AKT signaling pathway. Abstract : We are the first to show stimulatory effects of brain‐derived neurotrophic factor (BDNF) on proliferation and progesterone (P4 ) synthesis by bovine granulosa cells (GCs); and that the AKT signaling pathway participates in both proliferation and P4 synthesis induced by BDNF, while the ERK1/2 signaling pathway only participates in cellular proliferation. CCNA1: cyclin A1; CCND1: cyclin D1; CCNE2: cyclin E2; CDK1: cyclin‐dependent kinase 1; STAR: steroidogenic acute regulatory protein; MAPK: mitogen‐activated protein kinases; PI3K: phosphoinositide 3‐kinase